KESIAPAN SEKRETARIAT BAWASLU JABAR DALAM MENGHADAPI PEMILU DAN PEMILIHAN SERENTAK TAHUN 2024 - Barus, Eliazar (Jurnal Keadilan Pemilu, 2021)
Bawaslu's readiness is always tested by being faced with problems of election violations. This makes the election supervisory agency, in this case, the General Supervisory Agency (Bawaslu), have to work hard to deal with each of these problems. The General Supervisory Agency (Bawaslu) frequently faces many problems in the implementation of election supervision, one of which is the problem of systems and human resources. This paper employs a qualitative method in order to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals or groups of people. This study also makes use of secondary data sources derived from all literature pertaining to the General Supervisory Agency (Bawaslu) of West Java Province. The conclusion of this paper is that the preparedness of West Java's General Supervisory Agency (Bawaslu) Secretariat for the 2024 General Election can be seen through ve aspects: tangibles, dependability, responsiveness, assurance, and empathy. Based on the examination of these various aspects, it is possible to conclude that the General Supervisory Agency (Bawaslu) Secretariat's readiness for the 2024 election includes the dimensions of human resource readiness, system or procedure readiness, and facilities and infrastructure readiness.